Application of Interactive Visual Media in Learning Indonesian Vocabulary for Foreign Speakers for Grade VII Students at Nida Suksasat School, Thailand - Rahma Adawiyah; Syamsuyurnita Syamsuyurnita (Journal of General Education and Humanities, 2026)
The limited mastery of Indonesian vocabulary among foreign speakers is a major obstacle in the learning process of Bahasa Indonesia for Foreign Speakers (BIPA). This research aims to improve Indonesian vocabulary mastery of foreign-speaking students through the application of interactive visual media at Nida Suksasat School, Thailand. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart cycle model, comprising planning, action, observation, and reflection stages. The research subjects were 32 foreign-speaking students participating in Indonesian language learning. The research was conducted in two cycles following a pre-cycle stage to identify students’ initial vocabulary mastery. Data were collected through vocabulary tests, classroom observations, and learning documentation, and analysed using descriptive quantitative and qualitative techniques. The results showed a significant improvement in students’ vocabulary mastery, with learning completeness increasing from 31.25% in the pre-cycle to 62.5% in the first cycle and reaching 87.5% in the second cycle. In addition, the use of interactive visual media positively affected students’ motivation and active participation in learning. Therefore, the application of interactive visual media is effective and feasible as a learning strategy to improve Indonesian vocabulary mastery for foreign speakers.